Avoiding Laghw (Nonsense, Vain Talk, Vain Actions): An Initial Contribution to the Use of Islamic Concepts in Human Sciences (Mengelakkan Laghw (Tidak Masuk Akal, Perbincangan Kosong, Tindakan Tidak Baik): Sumbangan Awal Penggunaan Konsep Islam dalam Sa) - Seise, Claudia (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
This short academic note discusses the possibility of incorporating the Islamic concept of leaving laghw (nonsense, vain talk, vain actions) into the theoretical and/ or methodological frameworks of human sciences.